2017
DOI: 10.1534/g3.117.041277
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Design of Genome-Wide CRISPR/SpCas9 Knockout Screens

Abstract: The adaptation of CRISPR/SpCas9 technology to mammalian cell lines is transforming the study of human functional genomics. Pooled libraries of CRISPR guide RNAs (gRNAs) targeting human protein-coding genes and encoded in viral vectors have been used to systematically create gene knockouts in a variety of human cancer and immortalized cell lines, in an effort to identify whether these knockouts cause cellular fitness defects. Previous work has shown that CRISPR screens are more sensitive and specific than poole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
569
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 501 publications
(614 citation statements)
references
References 25 publications
16
569
2
1
Order By: Relevance
“…We identified features of protein complexes that underpin differences in recall between the two genetic perturbation datasets. Protein complexes recalled only in the CRISPR dataset were significantly depleted of core essential genes (Hart et al, 2015; Hart et al, 2017b), lower median gene expression levels, and had lower sequence conservation (Wilcoxon rank sum test, p < 1e-3) (Figure 2E, Table S3). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified features of protein complexes that underpin differences in recall between the two genetic perturbation datasets. Protein complexes recalled only in the CRISPR dataset were significantly depleted of core essential genes (Hart et al, 2015; Hart et al, 2017b), lower median gene expression levels, and had lower sequence conservation (Wilcoxon rank sum test, p < 1e-3) (Figure 2E, Table S3). …”
Section: Resultsmentioning
confidence: 99%
“…Core essential genes were defined as the union of the CEG1 (Hart et al, 2015) and CEG2 (Hart et al, 2017b) datasets. Gene expression data was taken from the CCLE RNA-seq data for these cell lines (Barretina et al, 2012), and human-mouse dN/dS was obtained from BioMart (Smedley et al, 2015).…”
Section: Star Methodsmentioning
confidence: 99%
“…Negative controls are essential for library design to evaluate experimental noise and the effects of the delivery of CRISPR reagents. Published libraries have often included non-targeting controls as 1%–5% of the total number of gRNAs in the library (Sanjana et al, 2014), but recent studies have suggested that gRNAs targeting non-essential genes can also serve this purpose (Hart et al, 2017). Alternative negative controls include targeting safe-harbor genomic regions (e.g., AAVS1 ) (Rosenbluh et al, 2017; Wang et al, 2014) as well as targeting GFP or luciferase in GFP- and luciferase-negative cells, respectively.…”
Section: Library Designmentioning
confidence: 99%
“…However, a number of gene-targeted studies have sought to identify essential genes in different cell types. These screens have, in general, identified similar sets of genes, although they also have found a smaller number of genes unique to a particular study and different relative essentiality ranks among genes identified in multiple studies (Hart et al, 2017; Rauscher et al, 2017a). It remains unclear whether these discrepancies are due to cell-type-specific effects, experimental artifacts, or differences in computational analysis of screen data.…”
Section: Pitfalls Of Pooled Crispr Screeningmentioning
confidence: 99%
See 1 more Smart Citation